EXPERIMENTAL RESEARCH OF NEW GENERATION SOLAR CELLS - N.S. Buktukov,; K.A. Vasin, (Academic Journal of Physical and Chemical Sciences, 2019)
Experimental work was done on a physical model of a solar photovoltaic battery with very high technical and economic efficiency due to the dispersion and focusing of solar radiation by wavelengths and due to the installation of various photocells at each wavelength. Experimental data and their processing showed that the power of the proposed design of the solar cell in terms of photoconverters is 1.46-1.48 times higher compared to the use of gallium arsenide according to conventional technology, and 4.15-4.2 times higher than single-crystal silicon. Moreover, the proposed solar cells require much less photocells, which significantly increases economic efficiency.